Effect of lysine supplementation on hypertensive men and women in selected peri-urban community in Ghana - Frederick Vuvor; Husein Mohammed; Thomas Ndanu; Obed Harrison (BMC Nutrition, 2017)
Abstract Background Lysine is one of the essential amino acids and in cereal based diets it is known to be the most limiting and therefore determines the quality of dietary protein in such diets. This study investigated the effect of lysine supplementation on blood pressure of hypertensive adults in selected peri-urban community in Accra, Ghana. Methods The study was a randomized double-blind controlled study made up of adults men and women assigned to a lysine supplemented group and a placebo-supplemented (control) group. The subjects aged between 18 – 45 years and totaling 180. Results Total of 50 (28%) of the participating were hypertensive defined as Systolic Blood Pressure (SBP) ≥140 mmHg. The mean SBP of lysine-supplemented group significantly dropped from 146.11 ± 11.92 to 128.95 ± 10.44 mmHg (p = 0.02). That of women also dropped from 144.12 ± 10.41 to 132.28 ± 10.69 mmHg, (p = 0.06 while the control group had there SBP remained fairly constant after 112 days of intervention with changes in men from 145.79 ± 12.56 to 142.79 ± 11.07 mmHg (p = 0.32) and women in the control had very little drop from 145.15 ± 14.79 to 145.00 ± 17.93 mmHg (p = 0.96). Conclusion Lysine supplementation resulted in normalization/reduction of blood pressure of hypertensive subjects who have suboptimal lysine intake.